PERSEPSI MAHASISWA TENTANG PENGGUNAAN MEDIA TABLET GRAFIS DAN PEREKAM LAYAR DALAM PERKULIAHAN MATEMATIKA EKONOMI - Mahfudz Reza Fahlevi; Mitra Pramita (PROGRAM STUDI AKUNTANSI SYARIAH FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2021)
The pandemic of Covid-19 has had an impact on many fields, one of which is education. As a result of this incident, educators are now starting to switch to various and suitable online learning media for optimal learning activities, some of the media that can be used include the use of graphic tablets and screen recording applications. The purpose of this study was to explore students perceptions of the use of its. The method used is survey. The survey was given as many as 10 closed statements and 3 open questions. Furthermore, the analysis of the survey results which is described in depth is about 10 closed statements. The number of respondents involved reached 61 students. The results showed that the statement strongly agreed with the statement of the need to use pen tablets in economic mathematics lectures up to 80%. Furthermore, the results of responses from respondents to statements using screen recording applications can increase learning motivation up to 61%.